Ausstellung Klasse Kamp 1985. - Kunstakademie Düsseldorf (Düsseldorf : Kunstakademie Düsseldorf, 1985)
Duncklenberg, Jan ; Geismar, Jarg M. ; Göllmann, Frank ; Kastenholz, Marion ; Kastner, Bernd ; Knüfer, Friedrich ; Lennartz, Dieter ; Lieber, Axel ; Mundt, Wilhelm ; Pallanca, Heike ; Peuckert, Gudrun ; Rob, Andreas ; Röing, Johan ; Sturm, Hendrik ; Wangemann, Sven ; Werres, Birgit
Ausstellung Klasse Kamp 1985, Kunstakademie Düsseldorf, 1985
boek